2014
DOI: 10.1093/cercor/bhu263
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillations Underlie the Maintenance of Feature-Specific Information and the Contents of Visual Working Memory

Abstract: Visual working memory (VWM) sustains information online as integrated object representations. Neuronal mechanisms supporting the maintenance of feature-specific information have remained unidentified. Synchronized oscillations in the gamma band (30-120 Hz) characterize VWM retention and predict task performance, but whether these oscillations are specific to memorized features and VWM contents or underlie general executive VWM functions is not known. In the present study, we investigated whether gamma oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 72 publications
13
129
2
Order By: Relevance
“…The amnesic effects of targeted replay interruption via electrical stimulation (Girardeau et al, 2009;Ego-Stengel and Wilson, 2010) suggest that this link is causal, not merely correlational, and has previously been modeled as such by the authors (Fiebig and Lansner, 2014).…”
Section: Serial Position Effectmentioning
confidence: 86%
See 2 more Smart Citations
“…The amnesic effects of targeted replay interruption via electrical stimulation (Girardeau et al, 2009;Ego-Stengel and Wilson, 2010) suggest that this link is causal, not merely correlational, and has previously been modeled as such by the authors (Fiebig and Lansner, 2014).…”
Section: Serial Position Effectmentioning
confidence: 86%
“…We know that attractors are typically active Ͻ200 ms, so Figure 5 (inset) implies that a peristimulus EPSP of 1.5 mV magnitude is apparently sufficient for attractor activity in our model. Thomson et al (2002) measured EPSPs of local layer 2/3 pyramidal-pyramidal cell connections in rat cortex at 1.7 Ϯ 1.3 mV, whereas long range connections have been estimated to be one order of magnitude weaker (Gilbert et al, 1990). Because the temporal coordination of EPSPs is crucial in attractor operation, it is worthwhile pointing out that intraminicolumnar connection delays in our model (1.5 Ϯ 0.23 ms, see Spatial organization) are very similar to those reported by Thomson et al (2002) between layer 2/3 pyramidal neurons (1.5 Ϯ 0.3 ms).…”
Section: Demo 2: Multi-item Wm: List Learning Without Intermittent Rementioning
confidence: 99%
See 1 more Smart Citation
“…Vogel and Machizawa, 2004;Sauseng et al, 2009), MEG (e.g. Palva et al, 2010;Mitchell and Cusack, 2011;Honkanen et al, 2015;Siebenhuhner et al, 2016), and fMRI (e.g. Todd and Marois, 2005;McNab and Klingberg, 2008;Linke et al, 2011;Stevens et al, 2012;Ester et al, 2013;Vicente-Grabovetsky et al, 2014;Galeano Weber et al, 2016;Veldsman et al, 2017), with some differences reported across age groups (for a review see Sander et al, 2012).…”
mentioning
confidence: 99%
“…All elements in the derivation, then, are created as simple γ assemblies, and only some (namely, labeled phase heads) become more complex β assemblies; consider the difference between adverbs like nearly and verbs like ran. The rhythmic division of complexity which follows from this is supported by Honkanen et al (2014), who demonstrated that simple objects represented in visual working memory employ the γ band, while more complex objects are represented by the β band. This oscillatory procedure also matches the generative view that phase heads have a longer derivational life than non-phase heads (Boeckx, 2014a;Narita, 2014a).…”
Section: Formal Considerationsmentioning
confidence: 85%